New Paradigm Christianity and Commitment-formation: The Case of Hope Filipino (Singapore) - Cornelio, Jayeel (Archīum Ateneo, 2008)
What does religion mean to the individual? How are people religious and what do their beliefs, practices and identities mean to them? The individual's place within studies of religion has tended to be overlooked recently in favour of macro analyses. Religion and the Individual draws together authors from around the world to explore belief, practice and identity. Using original case studies and other work firmly placed in the empirical, contributors discuss what religious belief means to the individual. They examine how people embody what religion means to them through practice, considering the different meanings that people attach to religion and the social expressions of their personal understandings and the ways in which religion shapes how people see themselves in relation to others. This work is cross-cultural, with contributions from Asia, Europe and North America.